The prediction of resilience to alcohol consumption in youths: insular and subcallosal cingulate myeloarchitecture. Issue 11 (4th August 2022) - Weidacker, Kathrin; Kim, Seung-Goo; Buhl-Callesen, Mette; Jensen, Mads; Pedersen, Mads Uffe; Thomsen, Kristine Rømer; Voon, Valerie
Abstract: Background: The prediction of alcohol consumption in youths and particularly biomarkers of resilience, is critical for early intervention to reduce the risk of subsequent harmful alcohol use. Methods: At baseline, the longitudinal relaxation rate (R1), indexing grey matter myelination (i.e. myeloarchitecture), was assessed in 86 adolescents/young adults (mean age = 21.76, range: 15.75–26.67 years). The Alcohol Use Disorder Identification Test (AUDIT) was assessed at baseline, 1- and 2-year follow-ups (12- and 24-months post-baseline). We used a whole brain data-driven approach controlled for age, gender, impulsivity and other substance and behavioural addiction measures, such as problematic cannabis use, drug use-related problems, internet gaming, pornography use, binge eating, and levels of externalization, to predict the change in AUDIT scores from R1. Results: Greater baseline bilateral anterior insular and subcallosal cingulate R1 (cluster-corrected family-wise error p < 0.05) predict a lower risk for harmful alcohol use (measured as a reduction in AUDIT scores) at 2-year follow-up. Control analyses show that other grey matter measures (local volume or fractional anisotropy) did not reveal such an association. An atlas-based machine learning approach further confirms the findings. Conclusions: The insula is critically involved in predictive coding of autonomic function relevant to subjective alcohol cue/craving states and risky decision-making processes. The subcallosal cingulate is an essential node underlying emotion regulation and involved in negative emotionality addiction theories. Our findings highlight insular and cingulate myeloarchitecture as a potential protective biomarker that predicts resilience to alcohol misuse in youths, providing novel identifiers for early intervention.